The phenotype of type 1 diabetes in sub-Saharan Africa - Katte, Jean Claude; McDonald, Timothy J.; Sobngwi, Eugene; Jones, Angus G. (Frontiers in Public Health, 2023)
The phenotype of type 1 diabetes in Africa, especially sub-Saharan Africa, is not well understood. Most previously conducted studies have suggested that type 1 diabetes may have a different phenotype from the classical form of the disease described in western literature. There are numerous reports of low rates of islet autoantibodies amongst people with type 1 diabetes in African populations, which contradicts what has been published elsewhere. Also, some studies have reported high C-peptide levels in people diagnosed with type 1 diabetes suggesting significant endogenous insulin secretion. However, the majority of previously conducted studies have several limitations, including small sample sizes and the use of non-standardised methods. Furthermore, there are conflicting data between some dated and recently completed studies amongst young Africans with type 1 diabetes. Understanding the true phenotype of type 1 diabetes in sub-Saharan Africa is crucial for deciding on prevention and improved treatment strategies. In this review, we discuss previously published data on type 1 diabetes in sub-Saharan Africa and make comparisons with data from elsewhere while focusing on implications for care and research. We also highlight the challenges and context of type 1 diabetes care and research in sub-Saharan Africa.